Radiation dose comparison of transradial and transfemoral access in transarterial radioembolization and chemoembolization - Basar, Yeliz; Seker, Mustafa Ege; Guven, Koray (The European Research Journal, 2025)
Objective: To compare radiation doses associated with transradial access (TRA) and transfemoral access (TFA) in transarterial chemoembolization (TACE) and transarterial radioembolization (TARE) procedures for hepatic cancers. Methods: This retrospective, single-center study analyzed 119 patients who underwent TACE or TARE between October 2016 and October 2024. Radiation dose parameters were compared between TRA and TFA groups, including fluoroscopy time, fluoroscopy and fluoroscopy-digital radiography combined dose-area product (DAP), and total air kerma (AK). Statistical analyses were performed using the Mann-Whitney U test and Chi-squared test. Results: TRA was associated with significantly higher radiation exposure compared to TFA, including increased fluoroscopy time (median: 15.2 vs. 8.9 minutes, P<0.001), fluoroscopy DAP (median: 84.4 vs. 45.2 Gy∙cm², P<0.001), fluoroscopy-digital radiography combined DAP (median: 246 vs. 156.5 Gy∙cm², P=0.003), and AK (median: 959 vs. 612.9 mGy, P=0.001). No significant differences were observed in patient demographics, tumor localization, or treatment approach between the groups. Conclusions: TRA is associated with higher radiation exposure compared to TFA in TACE and TARE procedures. While TRA offers procedural benefits, further research is needed to optimize techniques and reduce radiation risks, particularly in interventional radiology.